Selected methodological problems in measuring the adhesive properties of surface layer - Kuczmaszewski, J. (Polimery, 2022)
Experimental procedures vised to study the adhesive properties of solid surface layers are reviewed with particular reference to contact angle measurements. The contact angle of distilled water on a PVC substrate was measured in relation to drop volume and time of contact of the drop with the substrate before measurement. The contact angle was found to be unaffected by drop volume (Fig. 3), but was affected by the time of contact reckoned from the moment of drop application to the moment of contact angle measurement (Fig. 5). The error of measurement was studied in relation to drop application mode (Fig. 4) and roughness of substrate surface. Possibilities were considered of modifying the adhesive properties of polymer material surface layers at the stages of polymer synthesis, processing and after-treatment. The properties are discussed in relation to selected structure parameters at the atomic, molecular, supramolecular and macroscopic levels like electronic work function, atom radius, lattice constant, ionization potential, polarizability, etc. (Tables 1, 2).